2000
DOI: 10.1116/1.1289541
|View full text |Cite
|
Sign up to set email alerts
|

Film growth precursors in a remote SiH4 plasma used for high-rate deposition of hydrogenated amorphous silicon

Abstract: The SiH4 dissociation products and their contribution to hydrogenated amorphous silicon (a-Si:H) film growth have been investigated in a remote Ar–H2–SiH4 plasma which is capable of depositing device-quality a-Si:H at 10 nm/s. SiH3 radicals have been detected by means of threshold ionization mass spectrometry for different fractions of H2 in the Ar–H2-operated plasma source. It is shown that at high-H2 flows, SiH4 dissociation is dominated by hydrogen abstraction and that SiH3 contributes dominantly to film gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
76
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 47 publications
2
76
0
Order By: Relevance
“…The films have been deposited by the remote expanding thermal plasma ͑ETP͒ under conditions in which film growth is dominated by SiH 3 and in which ion bombardment is absent. 14 The surface reactions are, therefore, purely chemical.…”
mentioning
confidence: 99%
“…The films have been deposited by the remote expanding thermal plasma ͑ETP͒ under conditions in which film growth is dominated by SiH 3 and in which ion bombardment is absent. 14 The surface reactions are, therefore, purely chemical.…”
mentioning
confidence: 99%
“…In previous articles, it has been demonstrated that the dissociation of SiH 4 in the ETP is either governed by ion-induced reactions for a purely Ar operated plasma source or by atomic hydrogen reactions when relatively high H 2 flows are added to the Ar. 3,24,29 In Fig. 1, an overview is given of the contribution to film growth of species that have been investigated in detail so far as a function of this H 2 flow.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows furthermore that at high H 2 flows ͑Ͼ7.5 sccs͒, the deposition rate can almost completely be explained by the contribution of SiH 3 radicals to film growth ͑estimated contribution ϳ90%͒. 3,24 The formation of SiH 3 is due to the hydrogen abstraction reaction HϩSiH 4 →SiH 3 ϩH 2 ͑1͒…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations